Hypoalphalipoproteinemia: Prevalence and the impact of treatment on reaching HDL cholesterol target level in patients with dyslipidemia (Faculty of Medicine Universitas Indonesia, 2001)
A low serum high density lipoprotein cholesterol (HDL-C) level is a potent predictor of coronary heart disease (CHD). It has beenÂ estimated that 11% of the Framingham men have isolated low HDL-C levels and about 30% of dyslipidemia patients have HDL-CÂ level of less than 35 mg/dl (hypoalphalipoproteinemia). In addition, there is uncertainty regarding the management of these patients.Â There is no epidemiological data on the prevalence low HDL-C level in dyslipidemia patients and the results of treatment on HDL-CÂ on a large number of patients in Indonesia. We conducted a survey in 13 cities in Indonesia to evaluate the prevalence ofÂ hypoalphalipoproteinemia among dyslipidemic patients and the impact of treatment with lipid modification drugs on achieving targetÂ level of HDL-C 35 mg/dl or more in routine clinical practice. A total number of 1420 dyslipidemia patients (mean age 50 years, maleÂ 58%) were included and analyzed in this report. The overall prevalence of hypoalphalipoproteinemia in our study was 35.4% and itÂ was correlated with the risk level of the patients; 21.9% among low risk group (patient with < 2 other risk factor), 39.6% in high riskÂ group (â¥ 2 other risk factors) and 44.3% in patients with CHD. After 12 week treatment, the prevalence decreased to 12%, 20% andÂ 18% in low risk, high risk and CHD patients respectively. The magnitude of HDL-C changes correlated inversely with base-line HDL-C and it was highest (59%) in the lowest HDL-C group (< 25 mg/dl) and the least change (23%) was found in group with the highestÂ HDL-C level (â¥Â 45 mg/dl). Only 46% of patients with low HDL-C value at baseline achieved normal HDL-C level after treatment. InÂ conclusion, the prevalence of low HDL-C in dyslipidemia patients was high especially in high risk group and in CHD patients. TheÂ majority of patients with low HDL-C at base-line could not reach the target level for HDL-C of 35 mg/dl or more after 12 weeksÂ treatment with lipid modification drugs. (Med J Indones 2001; 10: 98-102)Keywords: hypoalphalipoproteinemia, dyslipidemia, routine practice, anti lipid drugs